Massive Enlargement of the Tongue: A Report of Unusual Case - Reza Erfanian; Farrokh Heidari; Saeed Sohrabpour; Saeed Shakiba (Case Reports in Clinical Practice, 2022)
A 35- year- old woman presented with massive enlargement of the tongue. She had suffered this problem since a week ago when her tongue became enlarged with a sudden onset and eventually did not fit her mouth. Chronic tongue enlargement since childhood is noted. Patient had history of mental problems, namely cerebral palsy, and as she is not able to walk, she uses a wheelchair. Furthermore, due to severe scoliosis, right lung was atelectatic.Soon after initial assessments, she was carried to surgery room and as she could not lie down to supine position, was intubated in sitting position with a rigid laryngoscope. During the whole process, patient was sedated. Afterwards, tracheostomy was per- formed.After 5 days, no improvement in the size of tongue was observed. Diagnosis was revised in a medical commission and despite inflammatory pathology, the bulging tongue was resected.After recovery, patient could bear oral feeding and was dismissed with good general health. After a week, the devised airway created by tracheostomy was removed with- out any complication. During one-year follow up, no sequelae were observed.